Analisis Laporan Realisasi Anggaran Pemerintah Kota Medan - Cellya Cellya; Cinta Ummairo Agustin; Lidia Andika; Natalia Fitrita Lumban Gaol; Yesi Anastasia Tamba (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study explores the budget realization reports in the Medan City Goverment in 2020-2022, through an analytical descriptive approach. Involving a study of budget realization reports and interviews with relevant parties, this research explores the extent to which budget realization achievements meet predetermined targets and their impact on regional development. The analysis includes an evaluation of the relationship between the planned budget and the actual realization. In addition, the study identifies factors that influence budget performance and evaluates the implications of budget realization on regional development. The results of this study provide a comprehensive picture of the effectiveness and efficiency of budget management in the Medan City Goverment in 2020-2022. The findings are expected to make a valuable contribution in designing more responsive policies that support sustainable development at the local level.